Strengthening Strategy Village Performance Management In Effort Reducing Stunting Through Multistakeholder Involvement In The Village - Syahrinullah, Syahrinullah (SEAN Institute, 2024)
To support the acceleration of stunting control and reduction in Majene Regency, the government must provide guarantees for all families at risk of stunting in Majene Regency to receive sensitive and specific interventions implemented in the form of effective convergence so that all activities become a collaborative-synergistic multi-party movement with the hope that the implementation of convergence can run optimally. Research This use approach qualitative . Research location conducted in two villages namely Pesuloang Village and Adholang Dhua Village, District The Pamboang Regency Majene . Research time implemented in 2024. Determination informant through purposive sampling. The informants in study This that is informant key 2 people Acting Village Head , informant normal as many as 8 people consisting of from Secretary village , village PKK Mobilization Team , Human Development Cadre (KPM), Assistance Team Family (TPK), midwife village , Posyandu Cadres , BKB Cadres, IYCF Cadres and PAUD Units , PKH Facilitators , BPNT Facilitators and Extension Officers Agriculture is a stakeholder in the Village. Research Results This conclude that management performance village in effort stunting reduction is necessary done in a way comprehensive including Optimizing the Role and Coordination of Stakeholders in the Village, the Importance of Allocation The Right Budget Targets , Role of Cadres and Human Resources as the Spearhead of Intervention , Importance Program Innovation in Support Stunting Reduction and Monitoring and Evaluation as the Key to Program Success.